Kailee Bosch: capstone - Bosch, Kailee, artist (Colorado State University. Libraries, 2020)
The artist's statement: My practice as a maker began at the lathe. As a child, working in my fathers studio, I learned to make small functional objects: spinning tops, bowls, and the like. I grew up making and thinking about round wooden objects. While this history of woodworking is it at my core, I have expanded my vocabulary of materials and processes. In this body of work, I am focusing on three materials: wood, clay and bronze. I’m interested in wood for its continual push at precision, movable only with the right technique and tools. Clay is different. It is extremely pliable with the ability for endless additions and subtractions. It can be manipulated with the simple touch of my hand. Bronze, has another character. It is not easily moveable in its solid form, but when heated it transforms into a beautiful, viscous liquid that can be cast into endless shapes. Each of these materials is important, as are the process, craft and craftsmanship that give them form. I make both functional objects and speculative designs, playfully and with precision and rigor. I am interested in parts that make up a larger whole, connections, modules and systems. I think about the advantages and disadvantages of a given way of working, how the process gives shape to formal elements. I am seeking an interplay between traditional ways of making that value the hand and newer technologies that allow for precision, and repeatability. I am inspired by the Bauhaus, ideas of everyday design tied to craftsmanship and functionality. Works such as Marcel Breuer’s tubular steel furniture influence and inform my practice. Each of my works rely on both my hand as the maker, alongside a range of tools and machinery: computer controlled machining, 3D printed connections, laser cut extruder dies – the marks of each of these processes are recorded in the work. The result is a variety lines, layers and textures, as the hand turned wooden spindles, bronze cast connections, and cut and manipulated clay pieces, each display marks of the maker. Space and installation are also important; the interaction of objects with their surroundings. My designs respond to architecture and the body. My works build and reflect upon each other, with each material, process, and piece informing the next.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture